Legal Reform of Police Investigation Oversight in Realizing Accountable Law Enforcement Based on the Principles of Legal Certainty and Justice - Yudi Bintoro; Zainal Arifin Hoesein (Yayasan Pendidikan Tanggui Baimbaian, 2026)
This study aims to analyze the regulation and implementation of police investigation supervision in the Indonesian criminal justice system, identify legal weaknesses that hinder the realization of accountable law enforcement, and formulate a concept for legal reform of investigative supervision based on legal certainty and justice. The study employed a normative juridical method with a statutory and conceptual approach. The results indicate that current investigative supervision still faces various problems, including disharmony of regulations in the Criminal Procedure Code (KUHAP), the Police Law, and internal police regulations, limited authority of external supervisory institutions, weak independence of internal supervision, lack of integration of oversight mechanisms, and suboptimal use of technology in investigative supervision. These conditions have implications for continued abuse of authority, wrongful arrests, criminalization, non-transparent case terminations, and a high number of public complaints regarding the investigative process. Legal reform is needed through strengthening the authority of the National Police Commission (Komisi Nasional Polisi) as an independent supervisory institution, integrating internal and external supervision, implementing surveillance technology such as body-worn cameras and digital recordings of examinations, and establishing national standards for investigative accountability to achieve transparent, accountable, just, and legal certainty in law enforcement.